C-axis correlated pinning mechanism in vortex liquid and solid phases for Sm123 film with well-aligned BaHfO3 nanorods. (20th October 2017) - Awaji, Satoshi; Tsuchiya, Yuji; Miura, Shun; Ichino, Yusuke; Yoshida, Yutaka; Matsumoto, Kaname
Abstract: Nanorods, which are nano-scaled columnar-shape precipitates, have recently been used to improve critical current density J c in magnetic fields for REBa2 Cu3 O y (RE123, RE: rare earth element) high temperature superconducting tapes/films. However, the flux pinning mechanism of the nanorod is not clear yet. We investigated the J c and resistivity ρ properties in detail and discussed the flux pinning properties on the basis of the flux pinning state diagram for high-quality Sm123 films with well-aligned 5.6 vol% BaHfO3 nanorods. Plateaus were observed in the field dependence of J c and ρ at high temperatures above the delocalization temperature. This suggests that nanorod pinning becomes effective in the vortex liquid phase and it grows up when the temperature decreases toward the delocalization temperature. In the 'many-nanorod' state in the high temperature region above the delocalization temperature, double peaks in the F p curves appear due to the coexistence of nanorod pinning and random pinning. At low temperatures below 70 K, however, the well-scaled F p curves at low fields and temperature dependent (non-scaled) normalized F p curves are observed. From detailed analysis using the cooperation model of the random and the correlated pinning centers, we found that nanorod pinning is dominant below the matching field and the cooperation between nanorod pinning and random pinning determines the high field J c properties above the matching field.